2011
DOI: 10.1007/s10549-011-1482-6
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 is an independent prognostic marker for ER-positive breast cancer

Abstract: Forkhead box protein A1 (FOXA1) is a "pioneer factor" that plays a role in controlling nearly 50% of estrogen receptor target genes. FOXA1 expression correlates with estrogen receptor (ER)-positivity especially in luminal subtype A breast cancers. The aim of this study was to investigate the precise role of FOXA1 in breast cancer using a large population-based cohort. Nuclear expression of FOXA1 was analyzed in a tissue microarray of 4,444 invasive breast cancer cases using immunohistochemistry and correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 35 publications
10
103
1
3
Order By: Relevance
“…In this process, several pioneer factors can dynamically modulate chromatin openness in breast cancer cells (35). Among the known pioneer factors contributing to the estrogen response, FOXA1, GATA3, and PBX1 seem to play a role in ET resistance (36)(37)(38). In the HBCx34 TamR tumor, FOXA1 and GATA3 expression was increased, supporting the possibility of an epigenetic origin of the generalized ET resistance in this tumor.…”
Section: Discussionmentioning
confidence: 87%
“…In this process, several pioneer factors can dynamically modulate chromatin openness in breast cancer cells (35). Among the known pioneer factors contributing to the estrogen response, FOXA1, GATA3, and PBX1 seem to play a role in ET resistance (36)(37)(38). In the HBCx34 TamR tumor, FOXA1 and GATA3 expression was increased, supporting the possibility of an epigenetic origin of the generalized ET resistance in this tumor.…”
Section: Discussionmentioning
confidence: 87%
“…It was also reported that six miRNAs, including miR-1290, were upregulated in drug-sensitive cells following Y-Box protein 1 inhibition, but no differences in miRNA expression could be detected in multidrug-resistant gastric carcinoma cells (Belian et al 2010). FOXA1, a forkhead family transcription factor, has been reported to be expressed predominantly in luminal A breast cancer with favorable prognosis (Badve et al 2007, Mehta et al 2012. Hurtado et al recently reported that FOXA1 creates an open conformation at ER-binding sites and that ER can bind and activate target gene expression in the presence of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the expression of FOXA1 was positively correlated with ER-positivity, particularly luminal A type ER-positivity, and negatively correlated with tumor size, tumor grade, nodal status, the expression of Ki-67 and HER2 and basal-like subtype of breast cancer (31). A previous study reported that the expression of FOXA1 was positively correlated with ER + and PR + status, but inversely correlated with nuclear grade and the Ki-67 index, suggesting the therapeutic potentials of FOXA1 targeting (73).…”
Section: Luminal a Subtype Breast Cancer Therapeutic Potentialsmentioning
confidence: 99%